Hypandrium as a key character in resolving species-level taxonomy on the example of Perisama oppelii (Latreille) (Lepidoptera: Nymphalidae, Biblidinae) - Zubek, Anna; Lorenc-Brudecka, Jadwiga; Pyrcz, Tomasz W. (Zootaxa, 2015)
A detailed comparative study of the subspecies of Perisama oppelii (Latreille, [1809]) is carried out. Ten out of eleven subspecies are illustrated, including the females of P. o. bleuzeni Attal & Crosson du Cormier, 1996 and P. o. cristal Attal & Crosson du Cormier, 1996 for the first time. Male genitalia of P. o. amalia Oberthür, 1916, P. o. bleuzeni, P. o. cristal, P. o. erebina Oberthür, 1916, P. o. oppelii (Latreille, [1809]), P. o. viridinota Butler, 1873, and P. o. xanthica (Hewitson, 1868), as well as female genitalia of P. o. bleuzeni, P. o. cristal and P. o. oppelii are also presented for the first time. Based on the characters of hypandrium, a separate specific status is proposed for P. bleuzeni stat. n. Taxonomical value of the hypandrium is evaluated. The co-evolution of male and female genitalia is discussed.